IMPLEMENTATION OF A NON-SPLITTING FORMULATION OF PERFECTLY MATCHED LAYER IN A 3D – 4TH ORDER STAGGERED-GRID VELOCITY-STRESS FINITE-DIFFERENCE SCHEME - Skarlatoudis, A.A; Papazachos, C.B. (Bulletin of the Geological Society of Greece, 2010)
One of the major problems in numerical simulations of wave propagation in elastodynamics using grid-point methods is the truncation of the computational space by artificial boundaries. These boundaries produce spurious reflections, polluting the results with artificial noise, therefore several efforts have been realized in order to achieve transparent or non-reflecting boundaries for truncating the computational space. Perfectly Matched Layer (PML) has been one of the most efficient methods for implementing artificial boundaries at the edges of the computational models. However the application of PML requires the “tuning” of several variables, for which very limited work has been presented. In the present study we employ the Non-Splitting formulation of PML (NPML) technique presented by Wang & Tang (2003), based on the introduction of small perturbations in the wavefield. The NPML formulation shows the same accuracy with the originally introduced PML but is easier to be implemented because it does not require the field splitting. The main scope of this paper is to perform a full analysis of the efficiency of NMPL based on numerical tests using a 3D–4th order staggered-grid velocity-stress finite-difference scheme. The analysis consists of direct, quantified comparisons with reference solution waveforms from a semi-analytical method (Discrete Wavenumber Method) with synthetic waveforms produced using the most popular Absorbing Boundary Conditions (ABCs) and PML, in various canonical models (homogeneous and layer over half-space).